2003
DOI: 10.1046/j.1463-5224.2003.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects on the aerobic bacterial and fungal conjunctival flora of normal thoroughbred brood mares in Florida

Abstract: There were no significant differences between the number or type of organisms cultured during the sampling seasons in normal Florida horses. A large range of normal bacterial and fungal flora were isolated from these horses. The number of bacteria and fungi isolated are not uniform across seasons. The likelihood of detecting an organism depends on the horses' age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
159
6
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(188 citation statements)
references
References 12 publications
13
159
6
10
Order By: Relevance
“…is a gram-negative bacillus, considered as one of the most virulent pathogens of the cornea, with a prevalence between 6 and 14% among the microorganisms identified in corneal ulcers of horses (SAUER et al, 2003;KELLER & HENDRIX, 2005;WADA et al, 2010;WADA et al, 2010). As expected, this genus was not isolated in the present study; although, it was previously identified in the eyes of horses without ophthalmic problems (ANDREW et al, 2003;VIDAL et al, 2010;JOHNS et al, 2011).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…is a gram-negative bacillus, considered as one of the most virulent pathogens of the cornea, with a prevalence between 6 and 14% among the microorganisms identified in corneal ulcers of horses (SAUER et al, 2003;KELLER & HENDRIX, 2005;WADA et al, 2010;WADA et al, 2010). As expected, this genus was not isolated in the present study; although, it was previously identified in the eyes of horses without ophthalmic problems (ANDREW et al, 2003;VIDAL et al, 2010;JOHNS et al, 2011).…”
Section: Resultssupporting
confidence: 57%
“…Such discrepancy has been attributed to the ambient temperature and management to which the animal is subjected (PISANI et al, 1997;JOHNS et al, 2011); although, some authors have not identified any significant difference in the number or types of microorganisms isolated during different seasons of the year (ANDREW et al, 2003). Of the 200 samples collected in the present study, 131 (65.5%) showed bacterial growth (Table 1).…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations